The Role of in Vitro Culture Producing Secondary Metabolites and Plant Conservation Techniques to Overcome the Environmental Crisis - Sutini; Widiwurjani; Didik Utomo Pribadi; Nora Augustien (Nusantara Science and Technology Proceedings, 2022)
This paper aims to examine the role of in vitro culture as a technique to produce secondary metabolites that are needed in various fields. In addition to producing secondary metabolites, in vitro culture can also be used as a plant conservation technique that can produce plantlet asexually in large numbers. This large number of plantlets besides being commercialized, its growth and development of plants is useful for overcoming the decline in environmental quality. An example of a plant will be useful as the lungs of an area and its roots will reduce the erosion of land areas. The conceptual framework of this study is that in addition to producing secondary metabolites, in vitro culture also has a function for plant conservation which in the future can prevent environmental damage. The problem in this study is the instability in the secondary metabolite biomass production and the need for optimization in the domain of conservation techniques. The method of this paper writing was extracting data information from journals, books and online sources which being analysed descriptively and qualitatively to verify the data objectively. The result of this study showed the role of in vitro culture that can produce secondary metabolites and can be implemented in plant conservation that overcome environmental crises.